Новый вид клеща, обитающего на злаках в Среднем Поволжье (Trombidiformes, Siteroptidae) - Митрофанов, В.И.; Шабанова, Н.Ф.; Севастьянов, В.Д. (Вестник зоологии, 1984)
A New Grass-Dwelling Mite Species (Trombidiformes, Siteroptidae) from the Middle
Volga Area. Mitrofanov V. I., Shabanova N. F., Sevastianov V. D.— Vestn. zool., 1984,
No. 3. Siteroptes graminicola sp. n. is similar to S. avenae (Miiller), differs by short
external scapular chetae, closer position of external and internal crucial chetae bases, medial position of tarsus I proximal solenidium and other characters. The new species causes
spring wheat ear leucochroism.